2018
DOI: 10.1080/10408398.2018.1454400
|View full text |Cite
|
Sign up to set email alerts
|

Kale (Brassica oleracea var. acephala) as a superfood: Review of the scientific evidence behind the statement

Abstract: Kale (Brassica oleracea var. acephala) is a cruciferous vegetable, characterized by leaves along the stem, which, in recent years, have gained a great popularity as a ´superfood´. Consequently, in a popular culture it is listed in many ´lists of the healthiest vegetables´. Without the doubt, a scientific evidences support the fact that cruciferous vegetables included in human diet can positively affect health and well-being, but remains unclear why kale is declared superior in comparison with other cruciferous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
135
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(142 citation statements)
references
References 103 publications
1
135
1
5
Order By: Relevance
“…Characteristic compounds for Brassica plants are also glucosinolates, of which the hydrolysis products are associated with numerous health benefits [1]. Each type of Brassica shows a characteristic glucosinolates profile that includes more than ten different glucosinolates in each species/variety, although only three to four are predominant [2]. Previous studies have shown that vegetables from acephala group contain higher total glucosinolates content that other Brassica oleracea vegetables [26].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Characteristic compounds for Brassica plants are also glucosinolates, of which the hydrolysis products are associated with numerous health benefits [1]. Each type of Brassica shows a characteristic glucosinolates profile that includes more than ten different glucosinolates in each species/variety, although only three to four are predominant [2]. Previous studies have shown that vegetables from acephala group contain higher total glucosinolates content that other Brassica oleracea vegetables [26].…”
Section: Discussionmentioning
confidence: 99%
“…Kale and collards are higher in content of Ca, folate, riboflavin, and vitamins C, K, and A than other cruciferous vegetables [2]. They contain, same as other Brassica vegetables, phytochemicals from polyphenols, glucosinolates and carotenoids group whose presence in food is associated with antioxidant and anticancerogenic potential [2]. Production of Brassica vegetables from acephala group significantly increased, from 3994 to 6256 harvested acres, in the US in the period from 2007 to 2012, respectively [3].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Of the diverse species, Brassica oleracea (CC, 2n = 18) constitutes well defined group of economically and nutritionally important morphotypes, referred to as cole vegetables (kale, kohlrabi, cabbage, cauliflower, broccoli, brussels sprout) [52]. These Brassica vegetables are also termed as ‘super-food’ as they are vital source of secondary metabolites, antioxidants, vitamins and minerals [71, 16, 64, 69]. Among the cultivated B. oleracea varieties, cauliflower ( B. oleracea var.…”
Section: Introductionmentioning
confidence: 99%